Protection Law To Right Right Public Village In context Village Government - Askamaini, Askamaini; T Riza Zarzani (International Journal of Synergy in Law, Criminal, and Justice, 2024)
Village community rights are the rights that village residents have to participate in village governance, village development, village community development, and village community empowerment. Legal protection of the rights of village communities is important to ensure the fulfillment of these rights. In the context of village government, legal protection of the rights of village communities can be carried out in various ways, including, implementing transparent and accountable village government. This can be done by opening access to information to village communities, as well as providing opportunities for village communities to participate in decision making. Law enforcement against violations of village community rights. This matter can done with give strict sanctions to the violating parties rights public village. Empowerment public village . This matter can done with give education and training to public village as well as give access to public village For involved in activity economy .